Potencial de convergência regional em educaç\~ao no Brasil - Marcelo Medeiros; Luis Felipe Batista de Oliveira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– We analyze the factors determining educational inequalities within and between regions in Brazil. We are interested in how characteristics and the return to these characteristics in each region affect educational outcomes. For this we analyze the population of people aged 14 to 17 years in Brazil using PNAD data. By decomposing inequality in the effect of observed attributes, return to these attributes and residuals from the linear regressions used for prediction, we conclude that differences in the returns to the attributes are more important to inequality than differences in the distributions of attributes. Therefore, it is possible to reduce at least part of regional inequalities by means of educational policies if education in the worst off regions improves in the direction of the better off regions.
Keywords: I24; H77; 330; educational inequality; educational stratification; regional inequality; federalization of education